Gallbladder Emulating Hepatic Haemangioma on Gastrointestinal Bleed Scan - Kinza Abdul Hye; Muhammad Numair Younis (Journal of the Pakistan Medical Association, 2023)
Tc - 99m labelled erythrocyte scan is a sensitive method for detection of gastrointestinal (GI) bleed and liver haemangioma but false positive results can occur, as in this case gallbladder is visualized which is not a common finding. Single - photon emission computed tomography/computed tomography (SPECT-CT) is helpful to avoid such false-positive results. Keywords:GI bleed study, gallbladder visualization, SPECT-CT.